EXPLORING THE DEVELOPMENT AND STUDY OF SHAKESPEAREAN PERIOD IN UZBEKISTAN - Saodat Namozova (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article explores the intriguing development and scholarly exploration of the Shakespearean period in Uzbekistan, a nation not commonly associated with the English literary giant. Tracing the historical context, the narrative highlights the cultural richness of Uzbekistan and its role as a receptive ground for global literary traditions. The piece delves into the evolution of Shakespearean studies, examining how translations, academic institutions, and theater performances have woven the Bard's narratives into the fabric of Uzbek cultural discourse.